Durvalumab after chemoradiotherapy in stage III non-small cell lung cancer - Tomasini, Pascale; Greillier, Laurent; Boyer, Arnaud; Jeanson, Arnaud; Barlesi, Fabrice (Journal of Thoracic Disease, 2018)
Immune Check Point inhibitors (ICIs) have demonstrated efficacy in advanced stage solid tumors including non-small cell lung cancer (NSCLC), CTLA4, programmed cell death-1 (PD-1) and PD-1 ligand 1 (PD-L1) inhibitors being the most studied drugs.